Strategi MoU Snack Video: Analisis SWOT untuk Memaksimalkan Pendapatan Agensi Live Streaming - Halimah; Irawan; Sintani, Lelo; Harinie, Luluk Tri (SAFE-Network, 2025)
This study aims to analyze the marketing strategy through the Memorandum of Understanding (MoU) between the Snack Video application and live streaming agencies to increase revenue, and identify its strengths and weaknesses. With a qualitative approach through observation, interviews, and documentation, the study found that the implementation of the MoU had a significant impact on increasing agency revenue through four main indicators: Agency Revenue & Recruitment Task to recruit new hosts, Agency Host Active Task to increase host activity through training and incentives, Agency's Old Valid Host Task to maintain the loyalty of old hosts, and Agency Revenue Level Upgrade Task which reflects the optimal results of other strategies. The advantages of this strategy include effective incentives for host recruitment and activity, duration-based training, and a strong loyalty scheme. However, its weaknesses include complicated host validation, dependence on incentives, competition between agencies, and high revenue targets. The proposed solutions are marketing strategy diversification, service innovation, community strengthening, and market expansion. This study emphasizes the importance of simplifying the validation process and reducing dependence on incentives, while offering insights to improve the partnership model in the live streaming industry.